Building Tomorrow's Company - Leggart, Donald; Leggart, Donald (London : BBC Worldwide Ltd., 1999)
The building's company series introduces business leader's to the inclusive approach. The inclusive approach is not new, and is not yet another initiative.
series 1. Leadership - series 2. The customer relationship - series 3. The employee relationship - series 4. The investor relationship - series 5. The supplier relationship - series 6. Performance measurement - series7. The community relationship - series 8. communication
Keywords: Business